Natural Compounds as Antimicrobial Agents - Franco, Carlos M.; Vázquez Belda, Beatriz (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The world is full of plants and animals that have their own defenses, producing various substances in their daily fight against bacteria, fungi, or other agents. These products are alternatives to conventional antimicrobials that have a poor reputation with consumers. Many of these compounds are well known; however, the multiple types of structures together with the variable responses depending of the type of biocontrol needed in a wide range of applications, such as clinical, agricultural, general hygiene, and food, necessitates the continuous search for specific applications and the continuous study of how to use these substances. The present book provides a summary of reviews and original research works that explore the multiple alternatives for the use of these compounds.